Morning Wake-Up Habits and Student Discipline: A Case Study in an Indonesian Elementary School - Bait, Elmi Hanjar; Salim, Herli; Sudiapermana, Elih (International Conference on Elementary Education, 2025)
This study examines the influence of morning wake-up habits on student discipline at SDN Kareogenggong. Discipline, an essential component of character education, is reflected in punctuality, responsibility, and behavioral consistency. Using a quantitative correlational design, data were collected from 45 students through questionnaires, observations, and school records. The results show a strong and significant positive correlation between morning wake-up habits and key discipline indicators, including punctual arrival, task completion, and adherence to school rules (r = 0.779, p < 0.001). This study addresses an empirical gap by providing direct evidence that morning wake-up habits can serve as behavioral predictors of discipline—an area seldom explored in Indonesian elementary education. The findings suggest that structured morning routines at home and school may strengthen students’ character development and daily learning readiness